2016
DOI: 10.3389/fpls.2016.01823
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Roles of Melatonin on Redox Regulation of Photosynthetic Electron Transport and Synthesis of D1 Protein in Tomato Seedlings under Salt Stress

Abstract: Melatonin is important in the protection of plants suffering various forms of abiotic stress. The molecular mechanisms underlying the melatonin-mediated protection of their photosynthetic machinery are not completely resolved. This study investigates the effects of exogenous melatonin applications on salt-induced damage to the light reaction components of the photosynthetic machinery of tomato seedlings. The results showed that melatonin pretreatments can help maintain growth and net photosynthetic rate (PN) u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
67
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(79 citation statements)
references
References 44 publications
12
67
0
Order By: Relevance
“…), indicating that melatonin could counteract the reduction of D1 protein under environmental stresses, thereby possibly contributing to greater stress resistance in maize plants. Our results are consistent with a recent study, in which melatonin treatment could maintain the availability of D1 protein and improved the repair of PSII under salt stress in tomato plants (Zhou et al ). Our previous studies have demonstrated that CP29 phosphorylation was accompanied with the instability of PSII supercomplexes under environmental stress (Liu et al , Chen et al , ).…”
Section: Discussionsupporting
confidence: 94%
“…), indicating that melatonin could counteract the reduction of D1 protein under environmental stresses, thereby possibly contributing to greater stress resistance in maize plants. Our results are consistent with a recent study, in which melatonin treatment could maintain the availability of D1 protein and improved the repair of PSII under salt stress in tomato plants (Zhou et al ). Our previous studies have demonstrated that CP29 phosphorylation was accompanied with the instability of PSII supercomplexes under environmental stress (Liu et al , Chen et al , ).…”
Section: Discussionsupporting
confidence: 94%
“…For instance, Wang et al (2013) reported that-in addition to enhancing antioxidant enzyme activities-melatonin maintained the proper functioning of PSII in apple plants exposed to drought stress [58]. Melatonin also exerted beneficial effects on the ETC and other critical photosynthetic parameters in tomato seedlings exposed to salinity stress [59].…”
Section: Discussionmentioning
confidence: 99%
“…This evidence implies that exogenous application of melatonin could improve the antioxidant defenses (non-enzymatic and enzymatic) of plants mainly by removing the ROS generated by salt stress. Globally, the application of exogenous melatonin helps plants to better perform photosynthesis by avoiding chlorophyll degradation and stomatal closure, due to salt stress [221][222][223]. The application of exogenous melatonin (50-150 µM) in cucumber significantly improved plant responses to salt stress by increasing maximum quantum efficiency of PSII, chlorophyll levels and leaf net photosynthetic rate [216].…”
Section: Melatoninmentioning
confidence: 99%